STUDENT PERCEPTION OF FORMATIVE PEER REVIEW - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The present paper covers our initial research findings of postgraduate student perceptions of formative in-class peer review in relation to their presentations, research, professional communication, and language skills. The paper also aims to assess the impact it may have on learning at advanced level of language training, and explores how peer review approach used in classes changes student perception of its benefits and challenges and contributes to the development of presentation, language and research skills. Besides the development of speaking skills, critical thinking and argumentation, peer review enables them to assess themselves better, to think more about the target audience and encourages better course and research engagement and collaborative learning. In our research, the students were asked to provide in-class peer review of presentations made by students on various aspects of their research as part of the connected curriculum framework established at the University College London.